SARS-CoV-2 infections with emphasis on pediatric patients: a narrative review - Yamamoto, Lidia (2020)
This narrative review summarizes the main aspects underlying the new coronavirus SARS-CoV-2, its epidemiology, pathophysiology, pointing to differences of SARS-CoV-2 main receptors ACE2, in terms of expression and the amount of soluble ACE2 in the circulation of children, men and women, and also in those with risk factors such as the smokers and pregnant women or presenting with comorbidities (diabetes, obesity, hypertension and other cardiovascular diseases, renal and CNS pre-existing diseases). Clinical manifestations in adults and children were also described, emphasizing the particularities already seen in children, regarding signs, symptoms, viral excretion time and the involvement of all organs and systems. The COVID-19 in the pediatric population was divided into two sections: one dedicated to previously healthy children and adolescents with COVID-19, and the other to those who live with comorbidities and acquired COVID-19. A few paragraphs were reserved to the recently described severe multisystemic inflammatory syndrome associated with COVID-19 (MIS-C) that shares certain characteristics with Kawasaki disease. Some studies on the infection in pregnant and postpartum women, as well as neonates were shown. This review has also covered the laboratory diagnosis of COVID-19, passing through the imaging diagnosis made by the chest tomography revealing ground glass patching opacities, and results of non-specific exams such as the total blood with lymphopenia, the coagulation tests with increased prothrombin times, as well as marked increments of the D-dimer, troponin and proinflammatory cytokines. In the section devoted to the specific laboratory diagnosis of COVID-19, the most used RT-PCR protocols were described and some studies on the serological diagnosis with IgA, IgM and IgG detection were detailed, including the use of rapid immunochromatographic assays and discussing the ideal period after the onset of symptoms to perform each type of test. In the end, the management of pediatric patients with COVID-19 based mainly on supportive measures has been briefly commented.